A comparison of isolated and synthesized contingencies in functional analyses. Issue 3 (30th March 2020) - Holehan, Kathleen M.; Dozier, Claudia L.; Diaz de Villegas, Sara C.; Jess, Rachel L.; Goddard, Kelsey S.; Foley, Elizabeth A.
Abstract : Recently, researchers have compared the utility of isolated versus synthesized contingencies in functional analysis (FA) methodology (e.g., Fisher et al., 2016; Slaton et al., 2017). A limitation of these studies is that there were other differences across FA methodologies (e.g., design, contingency) that did not allow for isolation of the influence of isolated versus synthesized contingencies. Therefore, the current study compared outcomes of FAs that involved isolated versus synthesized contingencies for problem behavior of 5 children while controlling for these other differences across FAs (Experiment 1). Next, the current study compared the effects of interventions based on the functions identified in the isolated and synthesized contingencies for each participant (Experiment 2). Results indicated isolated contingency FAs produced differentiated responding for 1 or both functions for all 5 participants, and there were little to no differences between treatments informed by isolated and synthesized contingency FAs.